Long-term Effectiveness of Modified Electroconvulsive Therapy Compared With Repetitive Transcranial Magnetic Stimulation for the Treatment of Recurrent Major Depressive Disorder. Issue 6 (June 2016) - Jin, Xi-long; Xu, Wei-qin; Le, Ya-juan; Dai, Xiong-kai
Abstract : Abstract: This retrospective study recruited 150 patients with recurrent major depressive disorder (MDD) who received modified electroconvulsive therapy (MECT) and 150 cases treated with repetitive transcranial magnetic stimulation (rTMS), which aimed to compare the short- and long-term effectiveness, as well as economic outcomes, of MECT and rTMS with a large sample size in patients with recurrent MDD. The results showed that the response rate of patients in the rTMS group was lower than that in the MECT group (46.0% vs 58.7%, p < 0.05). Patients in the rTMS group had elevated rate of dizziness, but reduced rates of poor memory and headache, as well as lower costs compared with the MECT group ( p < 0.05). Importantly, we found that the relapse-free survival of patients was similar between the rTMS and MECT groups in the long term. In conclusion, rTMS is an alternative method for MECT in the treatment of patients with recurrent MDD.